Impact of minimal intervention techniques on the body mass index of preschoolers with early childhood caries, 1-year follow-up. - Moya-de-Calderón, Zaida (2022)
Objective: To determine the impact of Minimal Intervention Techniques (MIT) on the body mass index (BMI) of preschool children with early childhood caries (CIT). Material and Methods: Intervention, relational and longitudinal study. A random sample of 31 was obtained from a population of 100 pre-school children of both sexes and ages 3 to 5 who met the inclusion criteria. Anthropometric measurements were recorded: height- weight and BMI at the beginning, 6 and 12 months. The soft tissue oral examination revealed color changes and gingivitis; in hard tissues alterations of structure, chronology, sequence of eruption and the ceo-d index was applied; clinical evaluations were at baseline and at 12 months. Preventive MITs were applied: fluoride in varnish, microinvasive: ionomeric sealants and minimally invasive: Atraumatic Restoration Technique (ART). Results: The global and individual variations of the BMI at the beginning and 12 months after applying the IMR were highly significant (p <0.001). In finally evaluation, the clinical findings show positive and significant changes in mucosal color and degrees of gingivitis. 98% of preschool children presented CIT and ceo-d index on average 6.5% at the beginning and 1.7% after treatment, hypomineralization 45.2%, eruption delay 25.8%, alteration in the sequence and eruption chronology 29%. Conclusions: The progressive global and individual increase of the BMI is directly related to the application of the IMR; effective to regain oral health in preschool children with CIT over time.